2008
DOI: 10.1039/b805323e
|View full text |Cite
|
Sign up to set email alerts
|

Dunking doughnuts into cells—selective cellular translocation and in vivo analysis of polymeric micro-doughnuts

Abstract: Micron-sized polymeric "doughnuts" prepared via dispersion polymerization were found to be highly selective in their cellular translocation abilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…7 It has been demonstrated that the morphology of micro-/ nanoparticles can influence biodistribution, cellular uptake, cell internalization pathway, and drug release profile. [8][9][10][11][12] Similarly, surface charge and surface hydrophobicity have been shown to influence the stability of micro-/ nanoparticle suspensions, in vivo blood circulation time, biodistribution, protein adsorption, cellular uptake, and immune response. [13][14][15][16] However, the influence of morphology and surface properties has not been well understood due to the limited ability of existing micro-/nanoparticle preparation techniques to modulate these properties.…”
Section: Introductionmentioning
confidence: 99%
“…7 It has been demonstrated that the morphology of micro-/ nanoparticles can influence biodistribution, cellular uptake, cell internalization pathway, and drug release profile. [8][9][10][11][12] Similarly, surface charge and surface hydrophobicity have been shown to influence the stability of micro-/ nanoparticle suspensions, in vivo blood circulation time, biodistribution, protein adsorption, cellular uptake, and immune response. [13][14][15][16] However, the influence of morphology and surface properties has not been well understood due to the limited ability of existing micro-/nanoparticle preparation techniques to modulate these properties.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the torus structure might literally be a key structure that red blood cells can squeeze through narrow vessels by changing shape [18]. In addition, artificial torus particles showed the interesting in vivo results; they were detected solely in the liver region after intravenous injection into a mouse, and not in other organs without adverse effects [19].…”
Section: Introductionmentioning
confidence: 98%
“…Torus structures have previously been generated by several methods such as self-assembly of colloid particles on a hydrophobic liquid [20] or on superhydrophobic surfaces [21], consolidation in microfluids [15], phase separation dispersion during polymerization [19], or consolidation in spray drying [22]. Most methods, except for the polymerization, are based on asymmetrical consolidation mechanisms of solutions or suspensions.…”
Section: Introductionmentioning
confidence: 99%
“…While for two-dimensional non-elliptical inhomogeneities many analytical and numerical results have 'microdonuts' actively used in bioengineering [2]; (c) the toroidal shape of nanoparticles in BaTiO 3 [3]; (d) the formation of toroidal particles of SiO 2 in a Cu matrix due to internal oxidation of a Cu-Si solid-solution polycrystal [4].…”
Section: Introductionmentioning
confidence: 99%
“…Such inhomogeneities occur in both natural and man-made materials. Figure 1 provides several examples: toroidal particles represent the most desirable morphology of Li 2 O 2 deposition on a porous carbon electrode in lithium-oxygen batteries [5,6]; polymeric 'microdonuts' are used in bioengineering [2]; the toroidal shape of nanoparticles is reported to be preferred for the microwave absorption properties of BaTiO 3 [3]; Onaka et al [4] reported the formation of toroidal particles of SiO 2 in a Cu matrix due to internal oxidation of a Cu-Si solid-solution polycrystal.…”
Section: Introductionmentioning
confidence: 99%